Extension Du Reseau De Distribution D’eau Potable Dans Le District d’Abidjan - Yéradé Jeanne N’kongon (European Scientific Journal, ESJ, 2018)
The aim of the present study was to find a mechanism for funding the extension of the drinking water network to the poor neighbourhoods of the District of Abidjan in order to bring drinking water close to the disadvantaged populations. To this end, microeconomic data collected from one thousand households, spread over the entire territory of the Abidjan District, were used. A statistical analysis enabled the study to describe poor population’s access to drinking water and to highlight the inadequacies in the distribution of such a universal service. The use of type-II tobit model (the Heckman method) in analysing the data also enabled the study to identify the main explanatory factors for the district’s population’s willingness to pay (WTP) for the extension of the drinking water distribution network to their poor neighbourhoods. And average WTP for water extension in Abidjan is 140350 CFA francs per household and per year.